Tra neuroscienze e scienze umane. Qualche riflessione... con un po’ di ’polemos’ - Aprile, Luigi (Studi sulla Formazione/Open Journal of Education, 2011)
The author emphasizes the complexity of the issue in neuroscience today and how this issue has a strong interdisciplinary value. The author notes that as an argument for specialists, the problem of neuroscience has become a trendy topic, such is the pervasiveness of the argument of discussion at the level of popular science magazines, newspapers, mass media, like television , the radio, but also, to some extent, on the Internet(from social networking tools such as “You Tube”, etc..). The theme of neuroscience is so urgent that the author pres- ents some reflections on the relationship it has with psychoanalysis, social sciences and other disciplines.